2022
DOI: 10.1002/jev2.12188
|View full text |Cite
|
Sign up to set email alerts
|

K‐29 linked ubiquitination of Arrdc4 regulates its function in extracellular vesicle biogenesis

Abstract: Extracellular vesicles (EVs) are important mediators of intercellular communication. However, EV biogenesis remains poorly understood. We previously defined a role for Arrdc4 (Arrestin domain containing protein 4), an adaptor for Nedd4 family ubiquitin ligases, in the biogenesis of EVs. Here we report that ubiquitination of Arrdc4 is critical for its role in EV secretion. We identified five potential ubiquitinated lysine residues in Arrdc4 using mass spectrometry. By analysing Arrdc4 lysine mutants we discover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…ARRDC4KO mice have previously been shown to have defective extracellular vesicle release and sperm maturation ( 11 , 39 , 40 ). Here, we further show that ARRDC4KO mice exhibit low fasting glucose levels and cannot generate sufficient glucose following overnight fasting.…”
Section: Discussionmentioning
confidence: 99%
“…ARRDC4KO mice have previously been shown to have defective extracellular vesicle release and sperm maturation ( 11 , 39 , 40 ). Here, we further show that ARRDC4KO mice exhibit low fasting glucose levels and cannot generate sufficient glucose following overnight fasting.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the abscission of ARRDC1-containing microvesicles appears to be regulated by the VPS4 ATPase [ 219 ]. In addition to ARRDC1, the ARRDC4 protein may participate in the regulation of microvesicle biogenesis [ 220 , 221 ]. However, its mechanism of action is most likely not related to ESCRTs [ 220 ].…”
Section: Microvesicle Loading With Tnasmentioning
confidence: 99%
“…Ubiquitinated K270 has been identified by mass spectrometry, confirming that the Arrdc4 adaptor of the Nedd4 family of ubiquitin ligases, plays an important role in extracellular vesicle biogenesis. It has also been shown that NEDD4-2 poly-ubiquitiation of K-29-linked Arrdc4 at K270 is a possible new signal for ARRDC4-mediated release of extracellular vesicles [ 21 ]. The N-methyl-D-aspartate (NMDA) glutamate receptor plays important roles in the development and storage of information in the mammalian brain.…”
Section: Types Of Traditional Modifications and Their Biological Func...mentioning
confidence: 99%